A Qualitative Study of "online" Work Breaks. (2nd October 2019) - Kim, Sungdoo; Furst-Holloway, Stacie; Hollensbe, Elaine; Masterson, Suzanne; Sprinkle, Therese; Bologna, Daniele
ABSTRACT: Despite the growing empirical evidence on the beneficial effects of "micro" work breaks, scant research has examined "online" work breaks. Thus, the purpose of this study is to explore the nature and effects of online work breaks. Through an in-depth qualitative study of a diverse set of 33 full-time working professionals, we identified conditions under which online breaks occur as well as the characteristics and outcomes of these breaks. Interestingly, our findings point to both negative and positive outcomes associated with online breaks, largely dependent on an individual's ability to self-regulate. Our grounded theory approach allows us to develop a richer description of online work breaks and a theoretical model to help guide future research.